THE PHYTOCHEMICAL ANALYSIS AND ANTIOXIDANT CAPACITY DETERMINATION OF FIVE HYPERICUM SPECIES - ADEHUWA-OLABODE, Adaeze Adejoke; SAUTREAU, Asmita; VLASE, Laurian; VLASE, Ana-Maria; MUNTEAN, Dana (Studia Universitatis Babeș-Bolyai Chemia, 2022)
Medicinal plants are a valuable source of lead compounds and novel drugs. The Hypericum L. species traditionally treats skin wounds, sciatica, and depression. Presently, only a small percentage of the Hypericum species have been phytochemically characterised and 60% still requires analysis. Ethanolic and methanolic extracts were obtained by ultrasound assisted extraction and maceration extraction methods. Polyphenols, sterols, methoxyflavones, hyperforin and hypericin were detected through HPLC-MS analysis. ABTS assay was used to evaluate the total antioxidant capacity. H. maculatum and H. moserianum had the highest antioxidant capacity. The most abundant polyphenol in H. humifusum, H. moserianum and H. miracle-pistache was chlorogenic acid. For H. maculatum and H. perforatum, hyperoside and rutoside were the most abundant polyphenols. Sterols and methoxyflavones were quantified for the first time in all the species. β-sitosterol was the most abundant sterol across all species and ergosterol was absent in all species. Hispidulin was the only methoxyflavone (in small concentrations) found in all species except H. miracle-pistache. Hypericin was absent in H. moserianum and H. miracle-pistache and was most abundant in H. maculatum. Interestingly, H. miracle-pistache had higher concentrations of hyperforin than H. perforatum. The phytochemical profile of analysed Hypericum species prove to be a valuable bioactive’s source.